Risk Factors for Plantar Fasciitis in Physically Active Individuals: A Systematic Review and Meta-analysis. (May 2021) - Hamstra-Wright, Karrie L.; Huxel Bliven, Kellie C.; Bay, R. Curtis; Aydemir, Burcu
Context: Plantar fasciitis (PF) is a common condition in active individuals. The lack of agreement on PF etiology makes treatment challenging and highlights the importance of understanding risk factors for preventive efforts. Objective: The purpose of this systematic review and meta-analysis was to determine what factors may put physically active individuals at risk of developing PF. Data Sources: CENTRAL, CINAHL, EMBASE, Gray Lit, LILACS, MEDLINE (PubMed), ProQuest, Scopus, SPORTDiscus, and Web of Science were searched through April 2018 and updated in April 2020. Study Selection: Studies were included if they were original research investigating PF risk factors, compared physically active individuals with and without PF, were written in English, and were accessible as full-length, peer-reviewed articles. Study Design: Systematic review and meta-analysis. Level of Evidence: Level 3, because of inconsistent definitions and blinding used in the included observational studies. Data Extraction: Data on sample characteristics, study design and duration, groups, PF diagnosis, and risk factors were extracted. The methodological quality of the studies was assessed using the Strengthening the Reporting of Observational Studies in Epidemiology statement. When means and standard deviations of a particular risk factor were presented 2 or more times, that risk factor was included in the meta-analysis. Results: Sixteen studies were included in the systematic review and 11 risk factors in the meta-analysis. Increased plantarflexion range of motion (weighted mean difference [MD] = 7.04°; 95% CI, 5.88-8.19; P < 0.001), body mass index (MD = 2.13 kg/m 2 ; 95% CI, 1.40-2.86; P < 0.001; I 2 = 0.00%), and body mass (MD = 4.52 kg; 95% CI, 0.55-8.49; P = 0.026) were risk factors for PF. Conclusion: Interventions focused on addressing a greater degree of plantarflexion range of motion, body mass index, and body mass and their load on the force-absorbing plantar surface structures may be a good starting point in the prevention and treatment of active individuals with PF.